2018
DOI: 10.5267/j.msl.2018.5.001
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of heuristic algorithms to synchronized planning of machines and AGVs in FMS

Abstract: Flexible Manufacturing System (FMS) is a compound system containing essentials like workplaces, computerized storing and recovery systems, and material control devices such as automatons and automated guided vehicles (AGVs). In this paper, an attempt is made to study concurrently the machine and vehicle planning features in an FMS for minimization of the makespan. Planning is concerned with the distribution of partial resources to tasks over time and it is a resolution making procedure. It associates the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A previous study proved that the Palmer and Campbell Dudek Smith (CDS) heuristic methods show the minimum value of average of makespan and average utilization of machine [17]. Meanwhile, another study presented Dannenbring established a rapid access technique to syndicate the advantages of the Palmers slope index and the CDS [18]. This paper demonstrates three heuristic methods such as CDS, Palmer, and Dannenbring altogether.…”
Section: Introductionmentioning
confidence: 74%
“…A previous study proved that the Palmer and Campbell Dudek Smith (CDS) heuristic methods show the minimum value of average of makespan and average utilization of machine [17]. Meanwhile, another study presented Dannenbring established a rapid access technique to syndicate the advantages of the Palmers slope index and the CDS [18]. This paper demonstrates three heuristic methods such as CDS, Palmer, and Dannenbring altogether.…”
Section: Introductionmentioning
confidence: 74%
“…Golmohammadi et al (2016) proposed a meta-heuristic algorithm to deal with the problem of optimization of storage location and vehicle routing, aiming to decrease the logistics cost. Babu et al (2018) introduced a heuristic algorithm (HA) to deal with different kinds of scheduling problems in flexible manufacturing systems to minimize the makespan. Further, it has been found that the proposed heuristic algorithm provided a better optimal solution in less computational time.…”
Section: Literature Surveymentioning
confidence: 99%